Multi swarm optimization for following robot using RF communication - Lira, Sirajum Munia; Khan, Md. Mashood Iqbal; Badhon, Abdul Ahad Monwar (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.